IMPLEMENTASI ASESMEN NASIONAL DATA POKOK PENDIDIKAN (DAPODIK) DALAM PENINGKATAN KUALITAS PENDIDIKAN DI SMA MUHAMMADIYAH 2 MAJALAYA - Maulana, Yana; Nurhayati, Yeti; Maryam, Maryam; Yoseptry, Ricky; Ratnawulan, Tety; Adzani, Nesa Halimah (STKIP PGRI Situbondo, 2024)
The National Assessment of Basic Educational Data (Dapodik) at SMA Muhammadiyah 2 Majalaya determines the quality of education in designing strategies and policies, especially in data-based planning. This research is to find out whether there is implementation of the National Assessment of Basic Educational Data (Dapodik) in Improving the Quality of Education at SMA Muhammadiyah 2 Majalaya, and to illustrate how much the implementation of the National Assessment of Basic Education Data has increased in improving the Quality of Education, the research method used by the author is a qualitative approach research method, the research findings are Planning (planning function) technical planning starts from data collection on Basic Education Data (Dapodik) where the technical provisions stipulate that educational report cards and basic educational data are taken from the results of the National Assessment of Basic Educational Data, Organizing (organizing) forms a team implementing activities by arranging committees according to their main tasks, Implementing (Actuating) this National Assessment is actually the teacher preparing the equipment in the form of modules including physical teaching materials as student reading material in facing the National Assessment, Supervision (Controlling), carried out by KCD Region VIII and the West Java Provincial Education Office with the implementation of the National Assessment of Basic Educational Data (Dapodik), it can be concluded that the unit portrait Education can be described comprehensively according to actual conditions.